Comparison of normal and abnormal fertilization of in vitro‐matured human oocyte according to insemination method. Issue 4 (20th January 2016) - Park, Ju Hee; Jee, Byung Chul; Kim, Seok Hyun
Abstract: Aim: Our purpose was to compare the normal fertilization rate, multi‐pronuclei (PN) formation rate, and embryonic development of in vitro ‐matured oocytes between conventional insemination and intracytoplasmic sperm injection (ICSI). Methods: A total of 213 stimulated in vitro fertilization (IVF) cycles were selected, in which at least one immature oocyte was obtained (from 2010 to 2014). Immature oocytes were assigned to germinal vesicle (GV)‐stage or metaphase I (MI)‐stage oocyte groups. Cycles with obligatory ICSI due to male‐factor infertility were excluded. Cycles were divided into two groups according to fertilization method: there were 97 cycles with conventional insemination and 116 cycles with ICSI. After in vitro maturation of 324 GV‐stage oocytes and 341 MI‐stage oocytes, the fertilization rate, multi‐PN formation rate, and embryonic development were compared according to the fertilization method. Results: The normal fertilization rate was similar in the conventional insemination and the ICSI both in GV‐derived and MI‐derived oocytes. Both fertilization methods resulted in a similar multi‐PN formation rate in GV‐derived oocytes; however, in MI‐derived oocytes, the multi‐PN formation rate was zero with ICSI and this was significantly lower than that with conventional insemination (9.6%, P = 0.001). Conclusion: In non‐male‐factor infertility, ICSI should be considered when MI oocytes are matured.